Contrasting geographic patterns of genetic variation for molecular markers vs. phenotypic traits in the energy grass Miscanthus sinensis. Issue 5 (30th November 2012) - Slavov, Gancho; Robson, Paul; Jensen, Elaine; Hodgson, Edward; Farrar, Kerrie; Allison, Gordon; Hawkins, Sarah; Thomas‐Jones, Sian; Ma, Xue‐Feng; Huang, Lin; Swaller, Timothy; Flavell, Richard; et al.
Abstract : Species and hybrids of Miscanthus are a promising energy crop, but their outcrossing mating systems and perennial life cycles are serious challenges for breeding programs. One approach to accelerating the domestication of Miscanthus is to harness the tremendous genetic variation that is present within this genus using phenotypic data from extensive field trials, high‐density genotyping and sequencing technologies, and rapidly developing statistical methods of relating phenotype to genotype. The success of this approach, however, hinges on detailed knowledge about the population genetic structure of the germplasm used in the breeding program. We therefore used data for 120 single‐nucleotide polymorphism and 52 simple sequence repeat markers to depict patterns of putatively neutral population structure among 244 Miscanthus genotypes grown in a field trial near Aberystwyth (UK) and delineate a population of 145 M . sinensis genotypes that will be used for association mapping and genomic selection. Comparative multivariate analyses of molecular marker and phenotypic data for 17 traits related to phenology, morphology/biomass, and cell wall composition revealed significant geographic patterns in this population. A longitudinal cline accounted for a substantial proportion of molecular marker variation ( R 2 = 0.60, P = 3.4 × 10 −15 ). In contrast, genetic variation for phenotypic traits tended to follow latitudinal and altitudinal gradients, with several traits appearing to have been affected by divergent selection (i.e., Q ST >> F ST ). These contrasting geographic trends are unusual relative to other plants and provide opportunities for powerful studies of phenotype–genotype associations and the evolutionary history of M. sinensis .